2015
DOI: 10.11607/jomi.3614
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Simultaneous Maxillary Sinus Floor Elevation and Implant Placement with Residual Bone Heights Greater or Less than 5 mm

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
10
2
Order By: Relevance
“…38 Moreover, cortical bone thickness of the residual native bone is the main factor in selecting surgical procedures in sinus augmentation. 42 However, the results of the present study showed that CT values of reconstructed areas became stable about 1 year after the reconstruction, and cortical thickness did not reach that of the native bone for a long time. Nevertheless, the outcomes of the implants in the PCBM group were not different from those of the native bone group.…”
Section: Recent Research On Metabolic Bone Diseases Demonstrated Thatcontrasting
confidence: 75%
See 1 more Smart Citation
“…38 Moreover, cortical bone thickness of the residual native bone is the main factor in selecting surgical procedures in sinus augmentation. 42 However, the results of the present study showed that CT values of reconstructed areas became stable about 1 year after the reconstruction, and cortical thickness did not reach that of the native bone for a long time. Nevertheless, the outcomes of the implants in the PCBM group were not different from those of the native bone group.…”
Section: Recent Research On Metabolic Bone Diseases Demonstrated Thatcontrasting
confidence: 75%
“…Miyamoto measured cortical thickness using conventional CT and stated that cortical bone thickness, rather than cancellous bone volume, was the factor most strongly affecting implant stability at the time of surgery in native bone . Moreover, cortical bone thickness of the residual native bone is the main factor in selecting surgical procedures in sinus augmentation . However, the results of the present study showed that CT values of reconstructed areas became stable about 1 year after the reconstruction, and cortical thickness did not reach that of the native bone for a long time.…”
Section: Discussioncontrasting
confidence: 65%
“…13 A 44% failure rate of implants was reported in maxillary type 4 bone as a result of the trabecular bone content. 12 Pommer and colleagues, in a cadaver study, concluded that bone density seems to be the major determinant of primary stability in maxillary sinus augmentation with simultaneous implant placement, while RBH had no influence. 14 At the same time, cancellous bone exhibits faster remodeling and can be easily influenced by implant surface modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced bone quality generally does not facilitate the primary stability of implants; therefore, the posterior maxilla is associated with important risk factors that may jeopardize the survival of short traditional implants . A 44% failure rate of implants was reported in maxillary type 4 bone as a result of the trabecular bone content . Pommer and colleagues, in a cadaver study, concluded that bone density seems to be the major determinant of primary stability in maxillary sinus augmentation with simultaneous implant placement, while RBH had no influence .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation